Dakwah di Era Disrupsi (Studi Terhadap Rekayasa Global) - Abdul Rani Usman (UIN Antasari Banjarmasin, 2020)
Da'wah is a solicitation for good, commanding to the makruf and preventing the rebellion. Da'wah for Dinul Islam is a must for Muslims. Da'wah issued by the Prophet Muhammad SAW was continued by Ulul Albab and the preachers to be conveyed to mankind. Da'wah requires strategies and challenges following the phenomena of the times. At present the da'wah in the era of globalization has disruption related to the global geopolitics-economy that occurs, relating to global issues both human rights and politics. This study uses Berlo communication theory. This theory explains the source and receiver of messages about communication skills, attitudes, knowledge, social systems, and culture. This research uses library methods and content analysis. This research shows the da'wah developed by the preachers is plagued by issues of ISIS, radicalism, economic change, and global culture.